Proposal of a dynamic numerical approach in predicting flashover critical voltage - Ali. A. Salem; R. Abd-Rahman; M. S. Kamarudin; H. Ahmad; N.A.M. Jamail; N.A. Othman; M.T. Ishak; M.N.R. Baharom; S. Al-Ameri (Institute of Advanced Engineering and Science, 2019)
Glass insulators, due to its diverse characteristics, were used widely around the world for high voltage transmission lines. Surfaces of the insulators are exposed to high electrical, mechanical, and thermal stresses over the period of service. Accumulation of contamination distort stresses distribution along the insulators that may lead to flashover under severe condition. In this paper, Obenaus pollution model has been adopted to propose a dynamic mathematical modelling to determine flashover critical voltage with regard to parameters such as pollution conductivity, arc length, and width of layer of contamination on the surface of glass insulator. In addition, laboratory experimental works have been carried out according to IEC60305 to validate the results from numerical approach, which indicate a good agreement.